2019
DOI: 10.1021/acs.molpharmaceut.9b00006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Supersaturation Suppression in Dissolution Process of Acidic Drug Salt

Abstract: Supersaturable active pharmaceutical ingredients (sAPI), such as salts, cocrystals, and amorphous solids, can form supersaturated solutions after dissolving in the gastrointestinal fluids. However, there are cases in which supersaturation is not observed in an in vitro nonsink dissolution test. The purpose of the present study was to investigate the mechanisms of supersaturation suppression in the dissolution process of acidic drug salts. Diclofenac sodium (DCF Na, pK a = 4.0) was employed as a model drug. DCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The K sp (the drug-salt solubility product) value is at least required to simulate the dissolution of a salt. However, the dissolution mechanisms of a salt are not fully understood, especially the chemical reactions in the unstirred water layer [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The K sp (the drug-salt solubility product) value is at least required to simulate the dissolution of a salt. However, the dissolution mechanisms of a salt are not fully understood, especially the chemical reactions in the unstirred water layer [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the nucleation of free base particles occurs before starting precipitation in the small intestine [ 28 ]. However, there are many unknown factors in the nucleation process [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data showed a slower dissolution rate with ibuprofen sodium alone compared to dissolution rate when incorporated within the film. In each profile, it was observed that drug in its crystalline state achieved a condition of supersaturation due to the solubilizing effect of polymer combination ( 47 , 48 ). The dissolution profile of ibuprofen sodium showed a drug release of 59% at 15 min, while F5 had a drug release of 74%, a 1.25-fold increase ( p = 0.002), and F6 of 72%, a 1.22-fold increase ( p < 0.0001), resulting in an immediate-like release.…”
Section: Resultsmentioning
confidence: 99%